Diplomatic Differences: Official U.S. Reactions to the Moscow Show Trials, 1936-1938 - Welch, Jeanie; Evans, Kelly (Journal of Russian American Studies, 2023)
During Joseph Stalin’s Great Terror, the Soviet government conducted three show trials of leading government and Communist Party officials between 1936 and 1938. While much has been written about the Great Terror and the Moscow show trials, little attention has been paid to the contemporaneous reactions of the U.S. diplomats who were eyewitnesses to the proceedings. These diplomats were Ambassador Joseph E. Davies and Embassy Secretaries Loy W. Henderson, George F. Kennan and Charles “Chip” Bohlen. Davies and the Embassy Secretaries had differing views on the trials. Davies accepted the Soviet line that the defendants were guilty of these heinous crimes. In accepting the official Soviet line, Davies was in sharp contrast to the opinions of the Embassy Secretaries who were very skeptical and disbelieving in the charges and confessions. Ultimately the Embassy Secretaries were proven right with the revelations of Nikita Khrushchev’s “secret speech” in 1956 and with the later opening of the Soviet government and Communist Party archives after the fall of the Soviet Union. This paper discusses these differing views, based on official communiqués and on the later memoirs of these diplomats.